A new genus and species of Polynoidae (Annelida: Polychaeta) from the Canary Islands, and update on taxa present in the Northeast Atlantic - Núñez, Jorge; Barnich, Ruth; Monterroso, Óscar (European Journal of Taxonomy, 2022)
A new polynoid, Webbnesia maculata gen. et sp. nov., was discovered during benthic surveys conducted around the Canary Islands. Its generic characters (absence of cephalic peaks, ventrally inserted lateral antennae, reduced notopodium and chaetae all stout) place it close to Antinoe Kinberg, 1856, Hermadion Kinberg, 1856 and Malmgrenia McIntosh, 1874, but the combination is unique and justifies the erection of a new genus. The new genus and species are described, figured and discussed in detail. An updated list of taxa and an identification key to all genera of Polynoinae Kinberg, 1856 sensu lato currently reported from he extended Northeast Atlantic are given.
World Polychaeta Database (WPolyD).